Effects of Dietary Glutamine Supplementation on Heat-Induced Oxidative Stress in Broiler Chickens: A Systematic Review and Meta-Analysis - Chris Major Ncho; Vaishali Gupta; Yang-Ho Choi (MDPI AG, 2023)
In avian species, heat stress (HS) is usually the result of being exposed to high ambient temperatures, whereas oxidative stress (OS) results from the overproduction of reactive oxygen species. The current literature suggests that HS often leads to OS. Therefore, this systematic review and meta-analysis was conducted to assess the effects of dietary supplementation of glutamine on the antioxidant status and growth performances in heat-stressed broilers. A total of 13 studies were deemed eligible after an exhaustive search of the literature from Google Scholar, PubMed, and Scopus. Briefly, the following criteria were used to select the studies: trials performed on broilers; publication in peer-review journals using English as the text language; and sufficient details about the design and inclusion of dietary glutamine as a treatment for HS. Two main categories of outcomes were extracted from the studies included in the review: growth parameters and OS markers. For the meta-analysis, a random effect model was used when the heterogeneity was higher than 50%, and a fixed effect model was applied otherwise. Pooled standardized mean differences (SMD), and mean differences (MD) with their confidence intervals (CI) from the studies revealed that dietary glutamine could increase body weight gain (SMD = 0.70, CI = 0.50 to 0.90, p < 0.05), and feed intake (FI) (SMD = 0.64, CI = 0.43 to 0.86, p < 0.05), and reduce the feed conversion ratio (MD = −0.05, CI = −0.07 to −0.02, p < 0.05) in heat-exposed birds. Additionally, higher glutamine (SMD = 1.21, CI = 1.00 to 1.43, p < 0.05), glutathione (SMD = 1.25, CI = 0.88 to 1.62, p < 0.05), superoxide dismutase (SOD) (SMD = 0.97, CI = 0.58 to 1.36, p < 0.05), and catalase (SMD = 0.94, CI = 0.72 to 1.16, p < 0.05) levels were recorded in the serum, breast, and thigh muscle after supplementation of glutamine. Furthermore, the subgroup analysis revealed that malondialdehydes levels were decreased only in the serum (SMD = −0.83, CI = −1.25 to −0.41, p < 0.001) and thigh muscle (SMD = −1.30, CI = −1.86 to −0.35, p < 0.001) while glutathione peroxidase (GPX) activity was increased in the breast (SMD = 1.32, CI = 0.95 to 1.68, p < 0.05) and thigh muscle (SMD = 1.53, CI = 1.06 to 1.99, p < 0.05). Meta-regression models indicated that longer periods of heat exposure were inversely associated with the effectiveness of dietary glutamine in increasing FI, GPX, and SOD (p < 0.05). Besides, increasing the dietary concentration of glutamine led to higher GPX and SOD levels (p < 0.05). Taken together, results suggest that dietary supplementation of glutamine can effectively mitigate the deleterious effects of HS by enhancing the antioxidant status and increasing growth performances in broilers.